Avaliação do conhecimento, atitude e prática sobre a incontinência urinária e o impacto na qualidade de vida de mulheres praticantes de exercícios físicos - Coelho, Jucyara da Silva (2024)
Urinary incontinence (UI) is a problem that negatively affects women's quality of life and can be triggered or worsened by factors such as pregnancy, childbirth, and intense physical exercise. Therefore, understanding this condition is essential to promote adherence to preventive and treatment measures for UI. OBJECTIVE: The objective of this study was to evaluate knowledge, attitudes, and practices (KAP) regarding urinary incontinence and the impact on the quality of life of women who practice physical exercise. METHOD: This is a crosssectional study carried out with a population of women who practice physical exercise in Parnaíba, in Piauí. The sample consisted of 256 women aged between 18 and 67, selected by convenience. Data collection took place from March to July 2022, using an electronic form that included sociodemographic, gynecological, and obstetric information, as well as questions related to the level of physical activity (assessed by IPAQ), urinary complaints (through ICIQSF) and questionnaire on knowledge, attitudes and practices related to UI. Statistical analysis was performed using R software version 4.1.0. The chi-square or Fisher's exact test was used for categorical variables, and for numerical or ordinal variables, the Mann-Whitney and Kruskal-Wallis tests were used. RESULTS: The results demonstrated that of 110 women participants, 43% had urinary incontinence, with mixed urinary incontinence (MUI), the most common type, observed in 39.09% of participants. Among the urinary complaints presented, 63.64% of women reported losing urine at least once a week or less, in small quantities (82.73%), and 27.27% reported a moderate impact on quality of life. Regarding assessment (CAP), the majority had adequate knowledge (51.88%) and attitudes (98.74%), while preventive practices (83.58%) and treatment (70.47%) were inadequate. Many women said they had heard about UI (93.3%), pointed out some risk factors (66.1%), ways to prevent (83.3%) and treat (98.3%) UI. Furthermore, most participants showed appropriate attitudes by stating they felt comfortable reporting their urinary complaints to a male health professional (77.4%). However, most of these women reported never having carried out preventive practices to avoid urine loss (61.2%) and having sought help to treat urinary incontinence (70.5%). As secondary outcomes, a statistically significant association was observed between the number of pregnancies (p = 0.0042), mode of delivery (p = 0.002), and daily training time (p = 0.011) with UI. When comparing urinary complaints according to the type of physical activity, an association was observed between running and frequency (p = 0.019); the amount of urine loss (p = 0.042) and impact on quality of life (p = 0.042). CONCLUSION: Despite adequate knowledge and attitudes among the participants, they did not report adequate preventive practices and treatment. Furthermore, women who run had a higher frequency of urinary complaints and a moderate impact on quality of life.